Evaluasi Kinerja Guru Ilmu Pengetahuan Sosial Bersertifikasi Pendidik - Zulkarnain Zulkarnain; Widya Hestiningtyas (Mahesa Research Center, 2022)
The study aimed to evaluate the performance of social studies teachers at SMP certified educators in Way Kanan Regency, Lampung. The method used in this study is a qualitative descriptive method. The subjects of the research were 48 certified junior high school social studies teachers and 5 principals as respondents. Data collection tools used are questionnaire techniques, interview and documentation techniques. The data analysis technique used descriptive percentage. The results of the study show that the overall performance of socially-certified teachers is considered good when viewed from the indicators of the teacher's ability to implement and evaluate learning. However, the ability of teachers to plan lessons still needs to be improved. Recommendations given to teachers in preparing the Lesson Plan (RPP) should cover aspects of communication and information technology and be followed by the development of activities. As well as actively implementing the MGMP (Subject Teacher Consultation) program. Through this MGWP, it is hoped that teachers can improve learning methods, educational techniques on science and technology that can be used in classroom learning, share information, and improve teacher professionalism. Recommendations for local governments are to create self-development programs for teachers in order to develop and improve the quality of education.